SOCS5 contributes to temozolomide resistance in glioblastoma by regulating Bcl-2-mediated autophagy. Issue 6 (1st June 2022) - Yu, Jie; Han, Lin; Yang, Feng; Zhao, Mingliang; Zhou, Hong; Hu, Linwang
ABSTRACT: Temozolomide (TMZ) is the primary chemotherapeutic drug for treating glioblastoma (GBM); however, the final clinical outcome is considerably limited by the poor response and resistance to TMZ. Although autophagy is thought to be associated with chemotherapy resistance and cancer cell survival, the precise molecular mechanisms underlying this process remain elusive. The suppressor of cytokine signaling (SOCS) family is widely distributed in vivo and exerts a range of effects on tumors; however, the expression pattern and role of SOCS in GBM remains unknown. In this study, we determined that high SOCS5 expression level was associated with poor prognosis and TMZ resistance in GBM. TMZ induced an increase in SOCS5 expression level and upregulated autophagy during the acquisition of drug resistance. The observed increase in the extent of autophagy was mediated by SOCS5. Mechanistically, SOCS5 enhances the transcription of Bcl-2. Knockdown of SOCS5 inhibited TMZ chemoresistance in GBM cells through the inhibition of Bcl-2 recruited autophagy; upregulation of Bcl-2 blocked this effect. In summary, our findings revealed the involvement and underlying mechanism of SOCS5 in TMZ resistance. SOCS5 plays a critical role in GBM chemoresistance and may serve as a novel prognostic marker and therapeutic target for chemotherapeutically treating drug-resistant GBM. Graphical abstract: uf0001